KOKRISTALISASI KETOPROFEN-ASAM TARTRAT-NaCl UNTUK PENINGKATAN SIFAT KELARUTAN - Muhammad Taqiyyuddin Fahmi; Eka Deddy Irawan; Budipratiwi Wisudyaningsih; Kuni Zu’aimah Barikah; Yudi Wicaksono (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2024)
Ketoprofen is a drug compound with analgesic, anti-inflammatory, and antipyretic effects with very low solubility. The research aims to increase the solubility of ketoprofen using the cocrystallization method. Cocrystallization was carried out using a solvent evaporation method using a tartaric acid coformer and adding the inorganic salt NaCl. Cocrystal solids were characterized using PXRD, DSC, FTIR, and SEM. The cocrystals were evaluated for their solubility and dissolution in distilled water. The characterization results show that the ketoprofen-tartaric acid-NaCl cocrystal solid is a crystalline solid with different solid properties than the solid starting materials of ketoprofen and tartaric acid. Ketoprofen-tartaric acid-NaCl cocrystals showed significantly higher ketoprofen solubility and dissolution (p<0.05) than initial ketoprofen solubility and dissolution